2021
DOI: 10.1186/s12974-021-02178-z
|View full text |Cite
|
Sign up to set email alerts
|

Divanillyl sulfone suppresses NLRP3 inflammasome activation via inducing mitophagy to ameliorate chronic neuropathic pain in mice

Abstract: Background Chronic neuropathic pain is a frequent sequel to peripheral nerve injury and maladaptive nervous system function. Divanillyl sulfone (DS), a novel structural derivative of 4,4′-dihydroxydibenzyl sulfoxide from a traditional Chinese medicine Gastrodia elata with anti-nociceptive effects, significantly alleviated neuropathic pain following intrathecal injection. Here, we aimed to investigate the underlying mechanisms of DS against neuropathic pain. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 56 publications
2
25
0
Order By: Relevance
“…However, the level of NLRP3 expression was not affected. These results are consistent with a previous report suggesting that MCC950 blocks the assembly and formation of NLRP3, ASC, and caspase-1complex [ 15 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, the level of NLRP3 expression was not affected. These results are consistent with a previous report suggesting that MCC950 blocks the assembly and formation of NLRP3, ASC, and caspase-1complex [ 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…The NLR family pyrin domain containing 3 (NLRP3) inflammasome consists of NLRP3 protein, apoptosis-associated speck-like protein (ASC), and pro-caspase-1, which regulates IL-1β activation and secretion by active caspase-1. Thus, the dysregulation of the NLRP3 inflammasome is associated with various diseases, including ischemic stroke, diabetes, multiple sclerosis, atherosclerosis, Alzheimer’s disease, and other inflammatory-related diseases [ 13 , 14 , 15 , 16 ]. In addition, recent studies have revealed that dysregulation of NLRP3 inflammasome was associated with cognitive impairment [ 17 ], and the impairment could be reversed by inhibiting the NLRP3 inflammasome [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact regulatory mechanism between autophagy and pyroptosis in CFA-induced inflammatory pain is still elusive. Autophagy plays an important role in eliminating misfolded proteins, ROS, ATP and proinflammatory cytokines which induces NLRP3 inflammasome activation [ 47 ]. What's more, increasing evidence has shown that autophagy-related proteins can package and degrade the NLRP3 inflammasome components ASC and NLRP3 [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some indirect mechanisms by which autophagy suppresses inflammasome activation were also reported. Autophagy eliminates damaged or irreversibly depolarized mitochondria, thereby preventing the accumulation of endogenous inflammasome agonists, such as reactive oxygen species and damaged mitochondrial DNA (Plaza‐Zabala et al., 2017; Shao et al., 2021). Recent evidence indicates that autophagy plays a direct role in the regulation of inflammasomes.…”
Section: Discussionmentioning
confidence: 99%